UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI GROUP INVESTIGATION (GI) - Supriyadi, Teguh; Muhfahroyin, Muhfahroyin (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
Learning achievement is a students capability while and after accept learning experience learning. Learning process involved students activity is needed, so that Â to give the meaning and the real learning of students. GI cooperative learning model is a learning model involved whice all of students activity in learning process. In learning process the students find knowledge independenly because they are active and teacher just only as a facilitator. The conclusion of this research is the GI cooperative learning model can improve the result of study students XI IPA SMA Kosgoro Sekampung school year 2011/2012 fromÂ pre-classroom action research to the second cycle for 47,37% and researcher suggests that the GI cooperative learning model can be used to increase learning achievement of biology learning.Â Kata Kunci: Group Investigation, Aktivitas Belajar, Hasil Belajar